Traditional plants in forest gardens of West Kutai, Indonesia: Production and financial sustainability (Biodiversitas Journal of Biological Diversity, 2017)
Apuy M, Lahjie AM, Simarangkir B.D.A.S, Ruslim Y, Kristiningrum R. 2017. Traditional plants in forest gardens of West Kutai, Indonesia: Production and financial sustainability. Biodiversitas 18: 1207-1217. Our research on the first generation forest gardens (munaan) in West Kutai District, Indonesia, aimed (i) investigating the cultivation and the financial profit of various plants grown by the residents in the first generation forest gardens (munaan); (ii) finding out the financial feasibility level of the first generation forest gardens (munaan) cultivation by the residents. The subject of this research included farmers or people who cultivated the old/ first generation forest gardens as well as several plant commodities namely durian (Durio zibethinus), rambutan (Nephelium lappaceum), cempedak (Artocarpus champeden), langsat (Lansium domesticum), ihau (Dimocarpus didyma) (i.e. native Borneo longan), meranti (Shorea sp.) and kapur (Dryobalanops aromatica) trees. Five villages/kampongs were sampled, with each plot sized 20 m x 20 m. Biomass analysis stocks growth of meranti and kapur trees are using volume formula. While the fruit production was calculated by weighing the weight of the fruit. In order to find out the relationships among variables, a polynomial regression equation was employed to obtain the regression coefficient of determination (R2). The bioeconomic analysis feasibility was done by using Pay Back Period (PP), Net Present Value (NPV), Net B/C ratio and IRR. The amount of revenue level for each variant of fruit (i.e. durian, rambutan, langsat, ihau, and cempedak was different depending on the volume of fruit production and the selling price. The total amount of revenue from the cultivation of kapur and meranti trees depended on the total volume of timber, which was based on their diameter and basal area multiplied by the price of the timber itself. These findings imply that the cultivation of first generation forest gardens (munaan) was feasible for the community. The calculated values of Pay Back Period, Net Present Value (NPV), Net B/C and IRR at the discount level factor of 5% were 19.3 years; IDR 30.004.000, 1.58 and 8.8% respectively.
Keywords: Bioeconomic; cultivation; forest gardens